2022
DOI: 10.1111/tid.13955
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic allergy labels in immunocompromised populations

Abstract: Antibiotic allergy labels (AALs) are commonly reported, with well‐defined prevalence in the general population; several studies have now focused efforts on immunocompromised hosts. Understanding the prevalence of reported allergy labels and methods of antibiotic allergy evaluation and delabeling strategies has the potential to improve prescribing practices and clinical outcomes in this high‐antibiotic use group. In this review, we will discuss the current literature on the prevalence, impact, and evaluations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The positive impact of delabelling incorrect penicillin allergy labels have shown to be especially pronounced among susceptible populations such as the immunocompromised and elderly ( 37 40 ). Similar benefits have been observed upon delabelling of other non-penicillin antibiotics such as sulfa-antibiotics ( 41 , 42 ). Although prospective data remains limited, the compound benefits following the delabelling of multiple antibiotic allergies will undoubtedly be exponential.…”
Section: Efficacy Of Successful Antibiotic Allergy Delabellingsupporting
confidence: 65%
“…The positive impact of delabelling incorrect penicillin allergy labels have shown to be especially pronounced among susceptible populations such as the immunocompromised and elderly ( 37 40 ). Similar benefits have been observed upon delabelling of other non-penicillin antibiotics such as sulfa-antibiotics ( 41 , 42 ). Although prospective data remains limited, the compound benefits following the delabelling of multiple antibiotic allergies will undoubtedly be exponential.…”
Section: Efficacy Of Successful Antibiotic Allergy Delabellingsupporting
confidence: 65%
“…True rates of penicillin allergy are low. 45 Even in pre-lung transplant candidates with low lung volumes, PAST was well tolerated with no reported adverse events. 46 Studies of PAST demonstrated that up to 95% were successfully delabeled from their BLA, and subsequently, penicillins were safely administered in 51% of patients.…”
Section: New Challenge 2: Antibiotic Allergymentioning
confidence: 90%
“…47,48 Sulfa allergy, reported in 5%-11% of immunocompromised patients, has important implications as sulfonamides are commonly prescribed for prophylaxis against opportunistic infections including Pneumocystis jiroveci and toxoplasmosis. 40,45 One study described a protocol-driven approach for SOT patients and found that among 52 patients with reported non-anaphylactic reaction to sulfa medications, 92% successfully completed a desensitization protocol. 49 Among them, 80% continued to tolerate sulfamethoxazole-trimethoprim >3 months later without adverse events, resulting in an estimated cost savings of $575 per desensitized patient.…”
Section: New Challenge 1: Is Shorter (Antimicrobial Duration) Better?mentioning
confidence: 99%